The Medial Ventrothalamic Circuitry: Cells Implicated in a Bimodal Network - Vega-Zuniga, Tomas; Trost, Dominik; Schicker, Katrin; Bogner, Eva M.; Luksch, Harald (Frontiers in Neural Circuits, 2018)
Previous avian thalamic studies have shown that the medial ventral thalamus is composed of several nuclei located close to the lateral wall of the third ventricle. Although the general connectivity is known, detailed morphology and connectivity pattern in some regions are still elusive. Here, using the intracellular filling technique in the chicken, we focused on two neural structures, namely, the retinorecipient neuropil of the n. geniculatus lateralis pars ventralis (GLv), and the adjacent n. intercalatus thalami (ICT). We found that the GLv-ne cells showed two different neuronal types: projection cells and horizontal interneurons. The projection cells showed variable morphologies and dendritic arborizations with axons that targeted the n. lentiformis mesencephali (LM), griseum tectale (GT), ICT, n. principalis precommissuralis (PPC), and optic tectum (TeO). The horizontal cells showed a widespread mediolateral neural process throughout the retinorecipient GLv-ne. The ICT cells, on the other hand, had multipolar somata with wide dendritic fields that extended towards the lamina interna of the GLv, and a projection pattern that targeted the n. laminaris precommissuralis (LPC). Together, these results elucidate the rich complexity of the connectivity pattern so far described between the GLv, ICT, pretectum, and tectum. Interestingly, the implication of some of these neural structures in visuomotor and somatosensory roles strongly suggests that the GLv and ICT are part of a bimodal circuit that may be involved in the generation/modulation of saccades, gaze control, and space perception.